Risk factors for malnutrition in patients with nasopharyngeal carcinoma - Wang, Pengpeng; Soh, Kim Lam; Ying, Yanping; Liao, Jinlian; Huang, Xueling; Zhao, Huihan; Pan, Xiao; Deng, Lan; Yu, Xiaoxia (Springer Science and Business Media Deutschland GmbH, 2023)
Background: Malnutrition is a common complication in patients with nasopharyngeal carcinoma (NPC). However, there are few studies on risk factors for malnutrition in NPC patients. Our aims were to identify the risk factors for malnutrition in NPC patients. Methods: NPC patients were recruited in this cross-sectional study, and they were divided into well-nourished and malnourished groups according to the Global Leadership Initiative on Malnutrition (GLIM). Potential risk factors were initially screened using univariate analysis (p < 0.1), and the selected ones were analyzed by logistic regression analysis (p < 0.05) to identify the risk factors for malnutrition in NPC patients. Results: In total, 305 NPC patients meeting eligibility criteria were enrolled. Multivariate logistic regression analysis revealed that low body mass index (BMI) (OR = 0.596, 95% CI 0.520–0.683, p < 0.001), the high total radiation dose received (OR = 1.046, 95% CI 1.023–1.069, p < 0.001), appetite loss (OR = 2.839, 95% CI 1.269–6.353, p = 0.011), and low PA (OR = 0.993, 95% CI 0.988–0.998, p = 0.008) were risk factors for malnutrition in NPC patients. Conclusions: The low BMI, the high total radiation dose received, appetite loss, and low prealbumin were risk factors for malnutrition in NPC patients.